Estudo numérico do impacto da expansão urbana nas ilhas de calor em cidades do nordeste brasileiro - Santos, Ana Teena Bulcão dos (2024)
The growth of the urban population directly contributes to the increase in the number of cities and territorial expansion. As the urban perimeter has expanded in recent decades, a series of environmental problems have emerged or intensified in the urban climate, one of which is the urban heat island (UHI). The Brazilian Northeast is influenced by the trade winds, and its coastal region is influenced by the circulation of sea and land breezes. Therefore, it is necessary to investigate the interaction between the urban heat island (UHI) and the breeze circulation. The aim of this study is to use an atmospheric model to characterize the urban heat island for the coastal cities of Fortaleza and Natal and the impact of urbanization on urban areas and its effect on local circulation using the WRF atmospheric model and the dynamic downscaling method. Initial and boundary condition data from ERA-5 provided by the European Centre for Medium-Range Weather Forecasts (ECMWF) were used, with the simulation period being from 1 to 10 November 2019. Initially, the occurrence of nighttime urban heat islands was observed in the studied cities, with a peak heating of 3.5°C during the early hours, and the same behavior was observed in the WRF model simulation. Performing a spatial analysis of the simulation, it was observed that for Fortaleza, the UHI is limited to the city's extent, and this positive temperature difference during the night affects the mechanism of the land breeze circulation due to the ocean being at a temperature similar to the urban region. For the city of Natal, although the area of greatest intensity is concentrated in the city's central region, the land breeze is overlaid due to the intensity of the southeast trade winds in the eastern portion of the Brazilian Northeast. In the analysis of the wind field and vertical velocity at 850 hPa, it was possible to identify several regions of upward and downward movements within the city of Fortaleza, which may be related to urban breeze circulation. For the city of Natal, an upward current was observed under the Potengi River region and downward currents in its vicinity, indicating the occurrence of a river breeze that may contribute to the thermal comfort of the region. Regarding the study of the urban area expansion of the cities of Fortaleza and Natal, it was observed that as urbanization increases, the intensity of the urban heat island will also increase, resulting in a larger heated area. For Fortaleza, urbanization can affect the land breeze circulation, where a greater impact on surface heating was observed on the continental surface compared to the ocean. For the city of Natal, it was observed that there is an impact on the local climate, with warmer temperatures during the night and early morning. Regarding the local winds, no change in the circulation pattern was observed; however, if the urbanization process is more intense, it will have a greater impact on the local climate.